2023
DOI: 10.1038/s41561-023-01155-w
|View full text |Cite
|
Sign up to set email alerts
|

Extreme flooding controlled by stream network organization and flow regime

Abstract: River floods are among the most common natural disasters worldwide, with substantial economic and humanitarian costs. Despite enormous efforts, gauging the risk of extreme floods with unprecedented magnitude is an outstanding challenge. Limited observational data from very high-magnitude flood events hinders prediction efforts and the identification of discharge thresholds marking the rise of progressively larger floods, termed flood divides. Combining long hydroclimatic records and a process-based model for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Catchments in wetter climates experience sustained water supply which determines unvaried runoff‐generation processes. Conversely, river basins in drier areas, where longer lag times between rainfall events allow for the catchment to dry, undergo transient conditions leading to varied runoff‐generation processes (Basso et al., 2023). Our results confirm that explicitly accounting for the existence of different runoff‐generation processes enables us to adequately model the tail of flood distributions in catchments exhibiting flood divides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catchments in wetter climates experience sustained water supply which determines unvaried runoff‐generation processes. Conversely, river basins in drier areas, where longer lag times between rainfall events allow for the catchment to dry, undergo transient conditions leading to varied runoff‐generation processes (Basso et al., 2023). Our results confirm that explicitly accounting for the existence of different runoff‐generation processes enables us to adequately model the tail of flood distributions in catchments exhibiting flood divides.…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed data series range from 1951 to 2013, encompassing 36–62 (median: 59) hydrological years per basin (November to October). From this data set, we identified river basins exhibiting a sharp increase in the magnitude of rare floods (i.e., a flood divide in their empirical flood magnitude‐frequency curve, sensu Miniussi et al., 2023; Basso et al., 2023) by visually examining empirical flood‐frequency curves. In order to facilitate their identification from a large data set, we calculated the L‐skewness of the annual maxima sample (Hosking, 1990), which is a general and universal index for tail heaviness and robust to the presence of outliers (Vogel & Fennessey, 1993), we noticed that, for Germany, all the cases with L‐skewness exceeding 0.3 were also presenting this issue (Figure S2 in Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, nonlinear relationships between river morphology and long‐term erosion rates arise because erosional thresholds are exceeded more frequently as erosion rate and relief increase. The climate driver on river profile evolution is not the annual precipitation itself but how the soil water balance (Deal et al., 2018) and the hydrologic structure of watersheds (Basso et al., 2023) mediate flood frequency. These concepts place the central focus on water storage‐discharge relationships (Botter et al., 2009; Kirchner, 2009) to condition how rainfall events are converted to runoff ones.…”
Section: Introductionmentioning
confidence: 99%
“…Regional factors such as monsoon activity that experience anomalies in the form of direction and speed, the emergence of tropical disturbances (tropical cyclones, lowpressure areas, eddies, or the presence of Inter Tropical Convergence Zone-ITCZ), also contribute. Simultaneously, several local factors for instance local topography, elevation, atmospheric lability and local convective also have an impact (Basso et al, 2023). In 2007, a study analysing data spanning 22 years from 1982 to 2003 identified the primary factor behind floods in Indonesia as the occurrence of extreme wet weather systems (Chan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%